2019
DOI: 10.1002/humu.23933
|View full text |Cite
|
Sign up to set email alerts
|

Matching whole genomes to rare genetic disorders: Identification of potential causative variants using phenotype‐weighted knowledge in the CAGI SickKids5 clinical genomes challenge

Abstract: Precise identification of causative variants from whole-genome sequencing data, including both coding and noncoding variants, is challenging. The Critical Assessment of Genome Interpretation 5 SickKids clinical genome challenge provided an opportunity to assess our ability to extract such information. Participants in the challenge were required to match each of the 24 whole-genome sequences to the correct phenotypic profile and to identify the disease class of each genome. These are all rare disease cases that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…CAGI5 continued the emphasis on the interpretation of clinically relevant large‐scale sequence data, with a challenge on the risk of thrombosis in African‐American cohort given whole exome sequence (McInnes et al, ; Wang & Bromberg, ); the identification of variants contributing to intellectual disability phenotypes given gene panel sequence (Aspromonte et al, ; Carraro et al, ; Chen, ); and a challenge of matching whole genome sequences to clinical profiles for patients at Toronto's Hospital for Sick Children (SickKids) and identifying causal variants (Kasak, Hunter et al, ; Pal, Kundu, Yin, & Moult, ). The latter challenge is related to the CAGI4 SickKids challenge, also described in the assessment paper here.…”
Section: Introductionmentioning
confidence: 99%
“…CAGI5 continued the emphasis on the interpretation of clinically relevant large‐scale sequence data, with a challenge on the risk of thrombosis in African‐American cohort given whole exome sequence (McInnes et al, ; Wang & Bromberg, ); the identification of variants contributing to intellectual disability phenotypes given gene panel sequence (Aspromonte et al, ; Carraro et al, ; Chen, ); and a challenge of matching whole genome sequences to clinical profiles for patients at Toronto's Hospital for Sick Children (SickKids) and identifying causal variants (Kasak, Hunter et al, ; Pal, Kundu, Yin, & Moult, ). The latter challenge is related to the CAGI4 SickKids challenge, also described in the assessment paper here.…”
Section: Introductionmentioning
confidence: 99%
“…Group 4 (Pal, Kundu, Yin, & Moult, ) : The bioinformatics approach used by the group 4 resulted in five correct genome to patient matches: 17 (H), 56(N), 93(F), 95(C), and 99(B), and yielded candidate variants for each (Table , Table S3). Of note, ethnicity was stated for three of the five cases.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper has demonstrated that the use of specific HPO terms improves gene‐ranking with the top 10% of HPO terms being sufficient to rank the causative gene (Tomar, Sethi, & Lai, ). Unlike other submissions, SID#4 weighed the clinical terms by scoring the most serious and definitive (to a presumed disease) term in the profile with the highest value (Pal et al, & Moult, ). SID#8 built eight gene sets related to the diseases of interest and classified each case as belonging to one of those categories, rather than using all the genes associated with any of the HPO terms derived from the clinical descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…The GnomAD browser quotes a G559A allele frequency of 0.000008. Algorithms that speculate biological impact do not predict functional consequences, although these algorithms have a demonstrated need for improved reliability [12][13][14]. As such, it is appropriate that Invitae continues to cite G559A as a VUS.…”
Section: Discussionmentioning
confidence: 99%